Towards a better comparability during GMP assessment – Identifying the main parameters that influence the loss of volatile organic compounds from silicone elastomers. (December 2021) - Krüger, Oliver; Ebner, Ingo; Kappenstein, Oliver; Roloff, Alexander; Luch, Andreas; Bruhn, Torsten
Graphical abstract: Highlights: Conditioning step at 100 °C to remove sorbed water. Ventilation in the oven omitted for better comparability. Successful method evaluation study. Low measurement uncertainty of 25 %. Abstract: Silicone-based consumer products may contain volatile compounds, predominantly residual siloxane oligomers from production processes. To avoid unwanted release of these volatiles into food, postproduction removal by a tempering process is necessary and might be mandatory for consumer products – especially food contact materials (FCM). According to BfR recommendation XV tempering is assumed to be sufficient if the remaining volatile organic compounds (VOCs) represent less than 0.5 % of the total product weight, a value chosen 60 years ago indicating good manufacturing practice (GMP). However, the reproducibility and comparability of the respective gravimetric method results may be affected by several parameters including sample conditioning, ventilation in the oven and speed of sample handling. Based on the investigations reported in this work, a method evaluation study with an optimized and in-house validated procedure was conducted to assess its inter-laboratory reproducibility. According to the results, the gravimetric determination of the loss of volatile compounds is feasible with an expanded measurement uncertainty of 25 %.